2018
DOI: 10.20884/1.dr.2018.14.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Studi Pendahuluan Geologi Telaga Tirta Marta, Purbalingga, Jawa Tengah

Abstract: Abstrak-Telaga Tirta Marta terletak di Desa Karangcegak Purbalingga. Telaga ini dibentuk oleh satu titik keluran air tanah di permukaan dengan debit yang cukup tinggi. Selain itu terdapat titik-titik keluaran air tanah lain yang membentuk kelurusan di sepanjang kaki bukit. Keberadaan telaga ini juga menarik karena berada pada tatanan geologi yang lebih besar, yaitu Gunungapi Slamet. Publikasi dari hasil penelitian pendahuluan ini bertujua nmenganalisis faktor-faktor geologi yang mengontrol kemunculan mata air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…The low anomalous value around the volcanic cone on the CBA contour map is indicative of the position of the magma chamber of the young Slamet Volcano that is currently still active [2] . The high anomalous value in the northwest region of the volcanic cone is interpreted as andesite rock from the old Slamet Volcano [19] with a very high density. For further processing, the CBA data is reduced to a horizontal surface using the Taylor Series approximation, as described in the Methods [15] .…”
Section: Results Of Data Processionmentioning
confidence: 90%
“…The low anomalous value around the volcanic cone on the CBA contour map is indicative of the position of the magma chamber of the young Slamet Volcano that is currently still active [2] . The high anomalous value in the northwest region of the volcanic cone is interpreted as andesite rock from the old Slamet Volcano [19] with a very high density. For further processing, the CBA data is reduced to a horizontal surface using the Taylor Series approximation, as described in the Methods [15] .…”
Section: Results Of Data Processionmentioning
confidence: 90%
“…The two types of volcanic rock formations are estimated to have high-density values (Sedlak et al, 2009). According to Iswahyudi et al (2018), the lava deposits found in the Slope of Slamet Volcano area are a vesicular type with many cavities and cracks so that it can be drained by water, even several springs have sprung up in this area. The groundwater comes from the precipitation process, which collects in the rock cavities and cracks, then flows into the discharge area which has a lower elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Menurut beberapa peneliti terdahulu, struktur perlapisan berupa kontak antara batulempung dan breksi berpotensi menyebabkan longsor [5]. Struktur geologi terbukti menyebabkan longsor di daerah Karangkobar tetapi belum ada penelitian lebih spesifik mengenai potensi likuefaksinya [6]. Oleh karena itu, penelitian ini difokuskan untuk mengetahui pola stuktur yang bekerja dan potensi terjadinya likuefaksi apabila terjadi gempa bumi atau longsor.…”
Section: Pendahuluanunclassified